178k views
0 votes
-4(2x - 5) – (7 – 3x) = 4(x + 3)

User Jwwnz
by
4.5k points

2 Answers

4 votes

Answer:

x=1/9

Step-by-step explanation:

-4(2x-5) - (7-3x) = 4(x+3)

x=1/9

-4(2x-5) -(7-3x): -5x +13

4(x+3): 4x + 12

Subtract 13 from both sides

Simplify: -5x = 4x-1

Subtract 4x from both sides

Simplify -9x = -1

Divide both sides by -9

-9x/-9 = -1/-9

x=1/9

7 votes

Answer:

x = 1/9.

Step-by-step explanation:

-4(2x - 5) – (7 – 3x) = 4(x + 3)

-8x + 20 - 7 + 3x = 4x + 12

-8x + 3x - 4x = 12 + 7 - 20

-9x = -1

x = 1/9.

User Mobilewits
by
5.1k points